Preparation and Socialization of Population Administration Service Flow (Adminduk) in Temiyang Village, Kroya District, Indramayu Regency - Ayu Fitriyah; Didik Himmawan (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
The lack of information sources regarding the procedures and processes of administrative services related to population records that are accessible to the residents of Temiyang Village has led to a lack of understanding among the community about these procedures and processes. Through the creation of an X-Banner as an informational medium for population administrative services and by conducting socialization efforts, it is hoped that the residents of Temiyang Village will be able to easily access information about these procedures and thereby improve their understanding of population administrative services. The method used in this effort is qualitative, involving observation and interviews followed by socialization and the creation of informational media. Data collection in this activity is conducted through pre-tests and post-tests, which are then analyzed using the N-Gain Test to determine the category or level of audience understanding of the socialization material provided.